Perception of employees of industries in Malaysia on corporate sustainability in affecting customer confidence and loyalty: a case study - Kartina, Johan; Faiz, Mohd Turan; Wan Nurul Syahirah, Wan Lanang (Institute of Physics Publishing, 2017)
This paper aims to study the perception of the employees of industries in Malaysia on their companies in applying corporate sustainability as a concept in creating an ethical brand that strengthen consumer confidence and loyalty. A structure survey instrument is developed to study the employees’ perception on the company’s sustainable business practices in their companies. The targeted respondents are employees from various companies in Malaysia. The data obtained are analyzed and commented using spreadsheet analysis on the frequency and relative importance value. The results show good perception on their company’s sustainable business practices in becoming an ethical brand with the shared values’ of Malaysia being a country which supports Sustainable Development Goal initiatives (SDGs). The study also shows employees’ perception on reasons for businesses to incorporate sustainability concepts in their operations are in line with the Triple Bottom Line (TBL) principles with profitability as the strongest perceived reason. The findings indeed support future research in transforming Malaysia’s own domestic economy to a more sustainable direction.